Systemic Inflammatory Response Markers Associated with Infertility and Endometrioma or Uterine Leiomyoma in Endometriosis - Jing X; Li C; Sun J; Peng J; Dou Y; Xu X; Ma C; Dong Z; Liu Y; Zhang H; Shao Q; Zhang H; et al. (Dove Medical Press, 2020)
Xuanxuan Jing,1,* Chen Li,1,2,* Jintang Sun,1 Jin Peng,3 Yu Dou,4 Xiaofei Xu,3 Chao Ma,1 Zhaogang Dong,5 Yanguo Liu,6 Hui Zhang,3 Qianqian Shao,1 Hui Zhang,7 Lijie Wang,3 Yun Zhang,1 Xun Qu1 1Institute of Basic Medical Sciences, Key Laboratory of Cardiovascular Remodeling and Function Research, Qilu Hospital of Shandong University, Jinan, Shandong 250012, People’s Republic China; 2Department of Radiation Oncology, Qilu Hospital of Shandong University, Jinan 250012, Shandong, People’s Republic of China; 3Department of Obstetrics and Gynecology, Qilu Hospital of Shandong University, Jinan, Shandong 250012, People’s Republic of China; 4Department of Stomatology and Institute of Stomatology, Qilu Hospital of Shandong University, Jinan, Shandong 250012, People’s Republic China; 5Department of Clinical Laboratory, Qilu Hospital of Shandong University, Jinan, Shandong 250012, People’s Republic China; 6Department of Medical Oncology, Qilu Hospital of Shandong University, Jinan, Shandong 250012, People’s Republic of China; 7Department of Pathology, Qilu Hospital of Shandong University, Jinan, Shandong 250012, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xun Qu; Lijie Wang Email quxun@sdu.edu.cn; wangljie@hotmail.comPurpose: The aim of this study was to find the most useful marker of endometriosis-related infertility and evaluate predictive and diagnostic values of systemic inflammatory response markers (preoperative white blood–cell subtypes, neutrophil:lymphocyte ratio [NLR], platelet:lymphocyte ratio [PLR], and monocyte:lymphocyte ratio [MLR]) and CA125 levels in endometriosis patients.Methods: This study comprised 662 women who had undergone laparoscopic surgery and been pathologically confirmed as having endometriosis and 83 patients pathologically confirmed with benign ovarian tumors. Related inflammatory factors in endometriosis complicated by infertility were analyzed via logistic regression analysis. Diagnostic values of the inflammatory response markers were obtained by receiver operating–characteristic analysis.Results: We firstly identified that lower NLR level was an independent risk factor of infertility. Serum lymphocytes were significantly higher in endometriosis patients, while serum CA125, NLR, MLR, and PLR were elevated. For differentiating endometriosis from other benign ovarian tumors, the combination of NLR and CA125 achieved greater sensitivity than CA125 alone. In addition, both CA125 and NLR were positively correlated with stage, oviduct adhesion, and diameter of ovarian ectopic cysts.Conclusion: NLR may be used as a simple and easily obtained predictive marker for endometriosis with infertility. Moreover, NLR can be a neoadjuvant biomarker for serum CA125 to diagnose endometriosis.Keywords: endometriosis, endometrioma, uterine leiomyoma, infertility, NLR, PLR, CA125